Human Security, Philanthropy, and Sustainable Development in Northern Nigeria the Role of Islam - Muhammad Sani Mukhtar; Aminu Umar; Sherif Abdul Raheem Ajiteru (CV Media Inti Teknologi, 2026)
Background: Poverty, food insecurity, inadequate healthcare, and unemployment are just a few of the many human security issues Northern Nigeria faces. Although Islamic philanthropy has traditionally contributed to social welfare, little is known about its systematic role in sustainable development and human security.Objectives: The purpose of this study is to investigate how Islamic charitable practices, such as zakat, waqf, and sadaqah, enhance aspects of human security and promote sustainable development outcomes in Northern Nigeria. Additionally, it looks for ways whereby state-led programs are enhanced by faith-based philanthropy.Method: The study integrates document analysis, thematic synthesis, and literature evaluation using a qualitative analytical methodology. While the function of Islamic philanthropy is investigated through its religious, social, and institutional contexts, human security is evaluated across economic, food, health, and social dimensions.Results: Results show that Islamic giving greatly reduces poverty, increases community stability, and promotes food and health security. While waqf and sadaqah offer long-term funding for emergency relief, healthcare, and education, zakat is the most effective tool. When taken as a whole, these tools serve as community-based social safety nets that support official development programs.Conclusion: By combining Islamic generosity with the human security framework, this study adds to the body of literature by providing conceptual and useful insights for practice and policy. These results can be used by governments and charitable organizations to improve human security and resource allocation. To further validate these insights, future study may include comparative studies and empirical data.